2000
DOI: 10.1007/bf03343767
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the sleep apnea syndrome in acromegaly population

Abstract: The prevalence of sleep apnea syndrome (SAS) in acromegaly is high. Consequences of SAS are serious and are associated with increased morbidity and mortality. The aim of this study was to assess the relative frequency and predictive factors for SAS in a group of patients with acromegaly (n=55). The presence of SAS was evaluated using the Polymesam device. Hormonal and clinical examination consisted of assessment of growth hormone, insulin-like growth factor I plasma levels, body mass index (BMI), neck circumfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 17 publications
3
48
0
6
Order By: Relevance
“…As in previous studies, predictive criteria in our patients were male gender (5, 7, 11), long duration of disease before diagnosis (i.e. R6 years), and large neck circumference (26,27). The preponderance of men with SAS resembles the trend in nonacromegalic patients.…”
Section: Discussionsupporting
confidence: 73%
“…As in previous studies, predictive criteria in our patients were male gender (5, 7, 11), long duration of disease before diagnosis (i.e. R6 years), and large neck circumference (26,27). The preponderance of men with SAS resembles the trend in nonacromegalic patients.…”
Section: Discussionsupporting
confidence: 73%
“…Diabetes mellitus is more prevalent in acromegaly than in the general population, greater in the Spanish acromegalic population (especially in those exposed to somatostatin analogues) than in New Zealand (20%) (4), but lower than in Canada (40% plus 22% glucose intolerance) (11). The sleep apnoea syndrome reportedly affects between 67% and 75% of acromegalic patients when investigated prospectively (29,30). This is much greater than the prevalence of 13% observed in our registry and presumably reflects a low awareness of the problem by many physicians, who do not specifically ask about snoring and sleep apnoea in all their acromegalic patients.…”
Section: Morbiditymentioning
confidence: 99%
“…Many studies showed higher frequency of SAS in active acromegalic patients with a positive correlation with GH/IGF1 levels (3,12,13). Conversely, in the study of Grunstein et al (1) only the presence of central apnoea (CA), but not the degree of sleep apnoea, was associated with the disease activity.…”
Section: Introductionmentioning
confidence: 96%